Martin Thomas McMahon military pass - McMahon, Martin Thomas, 1838-1906.
Military pass (January 6) issued to Mrs. Spalding, Mrs. Parker, and Mr. Davis for travel to Alexandria, Va., signed by Captain McMahon, aide to Gen. George B. McClellan, Army of the Potomac.
The printed pass shows the date as 1861 but historical evidence indicates that it probably was issued in 1862.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: McClellan, George Brinton, -- 1826-1885.; United States. -- Army of the Potomac; Military passes; Alexandria (Va.) -- History -- 19th century; United States -- History -- Civil War, 1861-1865.; Virginia -- History -- Civil War, 1861-1865.